A brief review of common mathematical calculations in therapeutic apheresis. Issue 5 (5th June 2019) - Staley, Elizabeth M.; Hoang, San T.; Liu, Hefei; Pham, Huy P.
ABSTRACT: Apheresis is defined as the removal of blood from the body, its separation into constituent components, and removal or manipulation of one of these components prior to intravascular return with or without the addition of replacement fluid. Patients undergoing therapeutic apheresis often have multiple comorbidities, potentially affecting their hemodynamic status. Thus, a thorough understanding of apheresis principles and calculations is required for the performance of safe, efficacious, and successful procedures. The performance of simple transfusions or red blood cell exchange procedures is additionally complicated by the difficulties inherent in the procurement of compatible blood products, and the emphasis on minimizing exposure to unnecessary blood products. It is essential that apheresis physicians be able to accurately evaluate the risks/benefits inherent in the procedural options and efficiently stratify patients to the optimal therapeutic modality. The formulas requisite for performing therapeutic apheresis calculations are herein reviewed.